2003
DOI: 10.1128/jvi.77.13.7367-7375.2003
|View full text |Cite
|
Sign up to set email alerts
|

Viral Escape from Dominant Simian Immunodeficiency Virus Epitope-Specific Cytotoxic T Lymphocytes in DNA-Vaccinated Rhesus Monkeys

Abstract: Virus-specific cytotoxic T lymphocytes (CTL) are critical for control of human immunodeficiency virus type 1 replication. However, viral escape from CTL recognition can undermine this immune control. Here we demonstrate the high frequency and pattern of viral escape from dominant epitope-specific CTL in SIV gag DNAvaccinated rhesus monkeys following a heterologous simian immunodeficiency virus (SIV) challenge. DNAvaccinated monkeys exhibited initial effective control of the SIV challenge, but this early contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
123
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 32 publications
6
123
0
3
Order By: Relevance
“…Whether the failure of prophylactic vaccination is due to the evolution of immune escape mutations during acute infection has been discussed (10,11,63). Although immune escape is rampant and is an important hurdle for HIV vaccine development (37), it is an insufficient explanation for the failure of the vaccinations discussed here (63).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the failure of prophylactic vaccination is due to the evolution of immune escape mutations during acute infection has been discussed (10,11,63). Although immune escape is rampant and is an important hurdle for HIV vaccine development (37), it is an insufficient explanation for the failure of the vaccinations discussed here (63).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the rate and frequency of viral escape from CTL can differ for different viral isolates. Barouch et al recently showed that seven of nine Mamu-A * 01 ϩ rhesus monkeys infected with SIVsmE660 demonstrated viral escape at both the Env TL9 and the Gag p11C, C-M epitopes (2). In contrast, only 1 of 15 Mamu-A * 01 ϩ rhesus monkeys infected with SHIV-89.6P demonstrated viral escape from p11C, C-M-specific CTL (3).…”
Section: Discussionmentioning
confidence: 99%
“…In Mamu-A * 01 ϩ rhesus monkeys, mutation at the Tat SL8 epitope predictably occurs during primary infection with SIVmac239 (1), but escape at the Env TL9 and Gag p11C, C-M epitopes occurs more slowly (2,3,8). Importantly, the rate and frequency of viral escape from CTL can differ for different viral isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural CTL responses were defined as HIVspecific CTL responses occurring in naïve macaques or macaques vaccinated against a different protein. A comprehensive metaanalysis of all documented CTL escape events was performed; in total, 35 CTL escape variants were analyzed (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Of these, 18 represented escape from a natural CTL response (12 occurred in naïve macaques, 6 in macaques vaccinated against a protein other than the one in which escape occurred) and 17 represented escape from a vaccine-induced memory CTL response.…”
Section: Resultsmentioning
confidence: 99%